The association between Compulsory Community Treatment Order status and mortality in New Zealand. Issue 1 (13th January 2023) - Beaglehole, Ben; Newton-Howes, Giles; Porter, Richard; Frampton, Chris
Abstract : Background: Compulsory Community Treatment Orders (CTOs) enable psychiatric medication without the need for consent. Careful scrutiny of outcomes including mortality is required to ensure compulsory treatment is evidence-based and ethical. Aims: To report mortality for patients placed on CTOs and analyse data according to CTO status, mortality cause and diagnosis. Method: Data for all patients placed under CTOs between 1 January 2009 and 31 December 2018 was provided by the Ministry of Health, New Zealand. Data included diagnostic and demographic information, dates of CTOs, and any dates and causes of death. Deaths were categorised into suicides, accidents and assaults, and medical causes. Mortality data are reported according to CTO status and diagnosis. Results: A total of 14 726 patients were placed on CTOs over the study period, during which there were 1328 deaths. The mortality rate was 2.97 on and 2.31 off CTOs (rate ratio 1.29, 95% CI 1.14–1.45; P < 0.01). The mortality rate for accidents and assaults was 0.44 on and 0.25 off CTOs (rate ratio 1.73, 95% CI 1.23–2.42; P < 0.01). The mortality rate for medical causes was 2.33 on and 1.90 off CTOs (rate ratio 1.22, 95% CI 1.07–1.40; P < 0.01). The suicide rate was 0.20 on and 0.15 off of CTOs (rate ratio 1.33, 95% CI 0.81–2.12; P = 0.22). Conclusions: Increased care and medication provided during compulsory treatment does not the modify the course of illness sufficiently to reduce mortality during CTOs. Higher mortality rates during CTO periods compared with non-CTO periods may reflect greater unwellness during CTOs.